Modeling Of Oil Flows In Langgak Field Pipeline - Revi Fernandiaz; Idral Amri; Panca Setia Utama (Journal of Earth Energy Engineering, 2019)
Abstract Congeal in the pipeline is one of the biggest problems faced by PT.SPR Langgak in piping crude oil from production wells to oil processing unit caused by decreasing oil temperature. The purpose of this study is to study the effect of environmental temperature on fluid temperature in the pipeline, study the effect of wind speed on fluid temperature in the pipeline and to determine the location of the occurrence of congeal in PT.SPR Langgak pipeline. Determining the location of the occurrence of congeal using the model T with analytical methods in the Matlab software is by entering parameters of pipe temperature, viscosity, density, fluid velocity, wind speed and environmental temperature. The congeal location was determined by model T obtained in the Zone C pipeline distance 44.9-449m with the average error model T is 1.88%. This model T can be applied provided the paraffin content is 15-60% and the pipe characteristics (pipe thickness, pipe diameter and pipe material) are the same.